Hamlet - Shakespeare, William; Thurber, Samuel; Mille, A. B. (Boston : Allyn and bacon, 1922)
Aldwych Theatre,Royal Shakespeare Company in "Hamlet," by William Shakespeare, directed by Peter Hall, sets designed by John Bury, costumes in collaboration with Ann Curtis, music by Guy Wolfenden, duel arranged by John Barton, lighting by John Bradley, music played by the Royal Shakespeare Wind Band.
In: Richard L. Coe Theater Programs Collection (Library of Congress).
Keywords: William Shakespeare, 1564-1616 -- History and criticism